If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10f + 13 = 11f Reorder the terms: 13 + 10f = 11f Solving 13 + 10f = 11f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-11f' to each side of the equation. 13 + 10f + -11f = 11f + -11f Combine like terms: 10f + -11f = -1f 13 + -1f = 11f + -11f Combine like terms: 11f + -11f = 0 13 + -1f = 0 Add '-13' to each side of the equation. 13 + -13 + -1f = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1f = 0 + -13 -1f = 0 + -13 Combine like terms: 0 + -13 = -13 -1f = -13 Divide each side by '-1'. f = 13 Simplifying f = 13
| 2/(x-5)-1/(x-5)=11/(x^2-25) | | -18-12d=14-8d | | 2x^2+5(2x)= | | -2r=-1.2+9.68 | | 3x-3(4)-2x(2)= | | X+1+7x=-71 | | 4-2x(2)= | | 5a+(-6)=18 | | 19.67-9.2w-8.38=4.33+8.2w | | -10+7x+4x=12 | | -3+4x+4x=85 | | 19/4x=1292 | | .12x+1.5=.15x+1.3 | | 102000-1.6x5/6 | | 3x-3(4)= | | -14.5q+4.95=-17.8q+10.56 | | x^4+(17x^3)+(80x^2)+(100x)+7.5=0 | | -3x+5-3x=-49 | | -10-13p=18-15p | | 10200-1.6x5/6 | | -10+11x= | | -8+7x-2x=12 | | -5+11x-5= | | 6x^2+x-1=1 | | 10200-1.6x5/6= | | 5b/11=8/11 | | 2s+5s-82s=22s | | -2/(x^2) | | 3(X+4)=2X-23 | | 13.00-7.28= | | -5n-19=-6n-13+3n | | 8=6x-4x+4 |